2016
DOI: 10.1519/jsc.0000000000001050
|View full text |Cite
|
Sign up to set email alerts
|

Standing Long Jump Performance With an External Focus of Attention Is Improved as a Result of a More Effective Projection Angle

Abstract: Investigators have recently demonstrated that standing long jump performance is enhanced when participants focus their attention externally instead of their leg action but found no differences when examining peak force. The purpose of this study was to examine kinetic and kinematic properties associated with the standing long jump that may explain disparities between an internal and external focus of attention. It was hypothesized that the external focus condition would exhibit greater impulse values and a mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 20 publications
4
34
1
Order By: Relevance
“…For example , Porter, Ostrowski, Nolan, and Wu (2010) found external focus (e.g., jump as far past the start line as possible) instructions enhanced standing long-jump performance compared with internal focus instructions (e.g., "extending your knees as rapidly as possible"). Further replication suggested that this improvement was associated with a more effective jump projection angle (Ducharme, Wu, Lim, Porter, & Geraldo, 2016). Maximum vertical jump and reach height was also improved when directing attention externally (e.g., object being reached for) compared to when internal focus (e.g., focus on reaching with fingers) instructions are provided (Wulf, Zachry, Granados, & Dufek, 2007).…”
mentioning
confidence: 89%
“…For example , Porter, Ostrowski, Nolan, and Wu (2010) found external focus (e.g., jump as far past the start line as possible) instructions enhanced standing long-jump performance compared with internal focus instructions (e.g., "extending your knees as rapidly as possible"). Further replication suggested that this improvement was associated with a more effective jump projection angle (Ducharme, Wu, Lim, Porter, & Geraldo, 2016). Maximum vertical jump and reach height was also improved when directing attention externally (e.g., object being reached for) compared to when internal focus (e.g., focus on reaching with fingers) instructions are provided (Wulf, Zachry, Granados, & Dufek, 2007).…”
mentioning
confidence: 89%
“…Researchers have shown that participants exhibit a mean projection angle of 468 when given an external focus condition compared with an internal (508) and a baseline (498) conditions during a standing long jump (6). Therefore, the difference in jump distance among conditions could be explained by the external condition producing a projection angle, which is closer to optimal, which partially supports the "constrained action hypothesis."…”
Section: Horizontal Jumpsmentioning
confidence: 85%
“…More recently, an external focus of attention has been shown to produce a projection angle that is closer to optimal (6). Researchers have shown that participants exhibit a mean projection angle of 468 when given an external focus condition compared with an internal (508) and a baseline (498) conditions during a standing long jump (6).…”
Section: Horizontal Jumpsmentioning
confidence: 99%
“…Participants. Three groups of people participated in this study: adults (20 healthy men aged 19 -23that were students of a university), normal children (20 healthy boys aged [7][8][9][10][11] and DCD children (20 boys aged 7-11 who were diagnosed by the researcher as DCDs). All children were selected from an elementary school.…”
Section: Methodsmentioning
confidence: 99%
“…Studies on adults have shown that, directing the learners' attention to an external cue (impact of the movement on the environment) is more effectual than an internal cue (body movement) (1)(2)(3) and causes more effective arousal (4). These results have been shown in tasks and sports skills such as balance in healthy people (5), balance in individuals with Parkinson disease (6), long jump (7), endurance activity (8), golf (9), volleyball (10), and Football (11).…”
Section: Introductionmentioning
confidence: 99%